2019
DOI: 10.3390/toxins11080470
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Toxin Selectivity between the Marine Pufferfish Takifugu pardalis and the Freshwater Pufferfish Pao suvattii

Abstract: To clarify the differences in toxin selectivity between marine and freshwater pufferfish, we conducted experiments in artificially reared nontoxic specimens of Takifugu pardalis (marine) and Pao suvattii (freshwater) using tetrodotoxin (TTX) and paralytic shellfish poison (PSP; decarbamoylsaxitoxin (dcSTX) or saxitoxin (STX)). T. pardalis specimens were administered feed homogenate containing TTX or dcSTX (dose of toxin, 55.2 nmol/fish) and P. suvattii specimens were administered feed homogenate containing TTX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 43 publications
0
37
0
Order By: Relevance
“…Toxins were extracted from the muscle, liver, intestine, gallbladder, and gonads of four male and six female C. valentini specimens ( Table 1 ) collected from Amami-Oshima Island in the Kagoshima Prefecture of Japan. Analysis of the extracts by liquid chromatography tandem mass spectrometry (LC-MS/MS) for TTX [ 9 , 26 ] revealed that samples from all tissues produced a peak with a retention time corresponding to that of the TTX standard in the chromatogram monitored at m / z 162 as a product ion with m / z 320 as a precursor ion (described as m / z 320 > 162 hereafter; a typical chromatogram is shown in Figure 2 ). Although TTX analogues were not included in the analysis because no standards were available, peaks estimated to be 4- epi TTX, 4,9-anhydroTTX, 11-deoxyTTX, and 11-oxoTTX were observed at m / z 320 > 162, 302 > 162, 304 > 162, and 336 > 162, respectively (typical chromatograms are shown in Figure A1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Toxins were extracted from the muscle, liver, intestine, gallbladder, and gonads of four male and six female C. valentini specimens ( Table 1 ) collected from Amami-Oshima Island in the Kagoshima Prefecture of Japan. Analysis of the extracts by liquid chromatography tandem mass spectrometry (LC-MS/MS) for TTX [ 9 , 26 ] revealed that samples from all tissues produced a peak with a retention time corresponding to that of the TTX standard in the chromatogram monitored at m / z 162 as a product ion with m / z 320 as a precursor ion (described as m / z 320 > 162 hereafter; a typical chromatogram is shown in Figure 2 ). Although TTX analogues were not included in the analysis because no standards were available, peaks estimated to be 4- epi TTX, 4,9-anhydroTTX, 11-deoxyTTX, and 11-oxoTTX were observed at m / z 320 > 162, 302 > 162, 304 > 162, and 336 > 162, respectively (typical chromatograms are shown in Figure A1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The peak intensities suggested that 4- epi TTX, 4,9-anhydroTTX, and 11-deoxyTTX were present in small amounts, while 11-oxoTTX was present at a higher level. When the same extracts were analyzed by high-performance liquid chromatography with post-column fluorescence derivatization (HPLC-FLD) for STXs [ 26 , 27 ], samples from each tissue, except for the female gallbladder, produced peaks at the retention times corresponding to those of neoSTX, decarbamoylSTX (dcSTX), and STX standards (a typical chromatogram is shown in Figure 3 ). No known components, such as C toxins and gonyautoxins (GTXs), were detected (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, the extract was partially purified with Bio-Gel P-2 column (Bio-Rad Laboratories Inc., Hercules, CA, USA) and the absorbed TTX was eluted with 0.05 M AcOH from the gel. The TTX fraction was analyzed by LC/MS/MS according to the method described by Nakashima et al (2004) and Gao et al (2019).…”
Section: Preparation Of the Ttx Containing Dietmentioning
confidence: 99%